An Individual-Based Model to Quantify the Effect of Salinity on the Production of Apocyclops royi (Cyclopoida, Copepoda) - Yoshino, Mizuki; Pan, Yen-Ju; Souissi, Sami; Dur, Gaël (Frontiers in Marine Science, 2022)
In this study, an individual-based model (IBM) was established and applied to simulate the effects of salinity variations on the productivity of a promising live feed cyclopoid copepod Apocyclops royi for aquaculture applications. The model integrates the effect of salinity on the different reproductive traits and temperature on female longevity. To calibrate the model developed on the Mobidyc platform, we collected data from previous literature and conducted complementary experiments. The model outputs on total nauplii production match the experimental results. Both showed a progressive increase in nauplii production from 0 up to 21 PSU, beyond which the production decreases. There were no significant differences between the estimated nauplii production and the observed ones for most salinity conditions. We then used the model to estimate the egg and nauplii production of a population initiated with 1,000 females along a salinity gradient from 0 to 39 PSU during 20-d cultivation. Around the optimal salinity of 21 PSU, the egg and nauplii production peaked at 1.8x105 eggs and 1.39x105 nauplii, respectively. A deviation of 7 PSU from the optimal salinity range would lead to a loss of 22 to 25% in egg and nauplii production. The results indicate that implementing the IBM into a life-cycle model provides useful tool for managing the risks of salinity variation on the copepod productivity in aquaculture conditions.